CHOP Regulates Endoplasmic Reticulum Stress-Mediated Hepatoxicity Induced by Monocrotaline - Guo, Yazhou; Yang, Chen; Guo, Rong; Huang, Ruijie; Su, Yongxia; Wang, Shuai; Kong, Yezi; Wang, Jianguo; Tan, Chengjian; Mo, Chonghui; Wu, Chenchen; Zhao, Baoyu (Frontiers in Pharmacology, 2021)
Monocrotaline (MCT), a pyrrolizidine alkaloid, is the major toxin in Crotalaria, which causes cell apoptosis in humans and animals. It has been reported that the liver is a vulnerable target of MCT. However, the exact molecular mechanism of the interaction between endoplasmic reticulum (ER) stress and liver injury induced by MCT is still unclear. In this study, the cytotoxicity of MCT on primary rat hepatocytes was analyzed by a CCK-8 assay and Annexin V-FITC/PI assay. Protein expression was detected by western blotting and immunofluorescence staining. As a result, MCT significantly decreased the cell viability and mediated the apoptosis of primary rat hepatocytes. Meanwhile, MCT could also induce ER stress in hepatocytes, indicated by the expression of ER stress-related proteins, including GRP78, p-IRE1α, ATF6, p-eIF2α, ATF4, and CHOP. Pretreatment with 4-PBA, an inhibitor of ER stress, or knockdown of CHOP by siRNA could partly enhance cell viability and relieve the apoptosis. Our findings indicate that ER stress is involved in the hepatotoxicity induced by MCT, and CHOP plays an important role in this process.